MATRIX STRUCTURE OF THE CONTROL SYSTEM OF A GAS TRANSPORTATION ENTERPRISE WITH THE DEMARCATION OF THE PLACE OF ECONOMIC EXPERTISE - Перевозова, Ірина Володимирівна; Чернова, Оксана Тарасівна; Морозова, Олена Сергіївна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
Modern challenges in the energy sector place high demands on transparent and flexible management of gas transportation enterprises. The importance of comprehensive controlling, which covers not only internal financial and production indicators, but also takes into account macroeconomic factors, is due to the complexity and interconnectedness of the gas distribution system of Ukraine. Any change in the operating mode of a separate element (pressure in the gas pipeline, production volumes) causes a chain reaction in all related links, which can have significant financial and economic consequences. In this context, the demarcation of the place of economic expertise in the general controlling system is of particular importance: it provides a deeper analysis of external risks, allows modeling market scenarios, taking into account regulatory requirements and price volatility on energy exchanges. The key structural elements that ensure integrated management are considered: organizational structure, financial and economic blocks, technical and production units and monitoring system. Along with this, the main components of controlling are highlighted, including operational and strategic analysis, risk management and personnel performance assessment. It is demonstrated that a comprehensive combination of these elements and approaches increases the level of readiness of the enterprise to external challenges, increases the transparency of costs and revenues, and also contributes to the optimization of gas transportation processes. Special attention is paid to the relationship with the general gas distribution system of Ukraine, where any technical or market change requires a quick analytical response. The use of controlling tools with economic expertise allows gas transportation enterprises not only to manage current operations more effectively, but also to form a strategic vision of development, based on accurate calculations, risk management and long-term planning. The results of the study can become the basis for the implementation of innovative approaches to management in the gas transportation industry and provide the necessary flexibility in a rapidly changing environment. The transcription of the matrix structure of the controlling system of a gas transportation enterprise with the democratization of the place of economic expertise is schematically presented.